Regret Is Born Where Choice Dies. (4th May 2022) - Ryan, Shane
Abstract: This paper analyses regret. On the basis of a number of examples, the case is made that regret is a negative affective state that has a perceived past choice as its object. More precisely, S regrets φ-ing, iff, and because (i) S has a negative affective state regarding φ-ing (Negative Affect State Requirement), the experience of which is explained by (ii) S perceiving that an alternative choice that was available to her would have been preferable to φ-ing (Perceived Forking Path Requirement). The resulting account is differentiated from Williams' agent-regret and shown to avoid problems faced by Zeelenberg's definition of regret.